CONTEMPORARY SIGHT AT AMLODIPINE AND NEW DRUGS OF S-AMLODIPINE - M. V. Leonova (Рациональная фармакотерапия в кардиологии, 2016)
Contemporary scientific data about mode of action of calcium channel blocker — amlodipine, its pleiotropic effect (influence on endothelial function and antiatherogenic action) is presented. Amlodipine reduces proliferation of vascular smooth muscle cells and extracellular matrix, improves the vasodilating function of endothelial cells although they have no L-type calcium channels. It puts into action through stimulation of nitric oxide (NO) secretion in endothelium. Results of experimental studies on the role of S- and R-isomers of amlodipine in hemodynamic and pleiotropic effects are presented. S-isomer is pharmacologically active blocker of L-type calcium channel while the R-isomer is responsible for NO release. Drugs based on S-amlodipine have been developed. Bioequivalence of the S-amlodipine and amlodipine in doses of 5 and 10 mg, respectively , is shown. Mean values of systolic and diastolic blood pressure, heart rate were not different significantly according to pharmacodynamic studies of S-amlodipine 5 mg and amlodipine 10 mg. S-amlodipine demonstrated better tolerability and lower incidence of ankle edema than amlodipine. Further long-term studies on S-amlodipine effect on hard endpoints are needed.